Studies on Synthesis, Characterization and Antimicrobial Activity of Some Oxocation Chelates of Pyrazolone Based Ligands - FERNANDEZ, ANNETTE; REMA DEVI, V.K; GEORGE, ANNIE (Asian Journal of Chemistry, 2010)
Some novel complexes of the ligands, 1-thiocarbamyl-3-methyl-4-( 4'-amino antipyrine hydrazono)-2-pyrazolin-5-one (HAATP) and 1-thiocarbamyl-3-methyl-4-(2' -amino phenol hydrazono)-2-pyrazolin-5-one (H2OATP) with VO(II) , UO2(II) and MoO2(II) have been prepared and characterized by elemental analysis, molar conductance and magnetic susceptibility measurements and various spectral studies. The ligands and their vanadyl complexes were screened for their antibacterial and antifungal activities.